Assessing The Acid Mine Drainage Potential of A Stockpiled Gold Bearing Sulphide Ore. - Koomson, Bennetta; Fosu, Shadrack; Brako, Blestmond Afrifa; Asiama, Elias Kwasi; Yanful, Ernest K. (Earth Sciences Malaysia (ESMY), 2024)
This work seeks to assess the acid mine drainage (AMD) potential of stockpiled sulphidic gold bearing ore that was left untreated for a period of four (4) years. The mineralogical composition of the stockpiled sulphidic gold ore was determined using X-Ray Diffractometry (XRD) and Reflected Light Microscope. The AMD potential and kinetic studies on the ore sample were determined using Acid Base Accounting (ABA) and Humidity Cell (ASTMD 5744). The XRD and microscope analyses showed that the gold ore contain arsenopyrite and pyrite as the major sulphide minerals. The ABA confirmed that the gold sulphide ore could be a potential source of AMD with respect to AMD marginal of safety if the ore is left untreated for a very long period. Humidity Cell kinetic analysis showed a possibility of mobilizing Arsenic (As) into the geoenvironment when there is a long period of oxidation of abandoned sulphide run-of-mine (ROM) ore.